Magic as a Form of Oppression Towards Women: Gender Ideology in Maleficent (2014) - Wendranirsa, Thalia Shelyndra (Paradigma: Jurnal Kajian Budaya, 2023)
Male and female are not only differentiated by their physical and emotional condition. There are many other aspects that can be explained to prove male and female differences, one of those differences can be seen by how they name colour. Using Lakoff’s theory, which talks about female and male differences in colour naming, as the main theory, this research is conducted. Using ten FIB UI English students as the sample, five males and five females, this research aims to prove Lakoff’s theory whether it is suitable with the condition of FIB UI English students or not. Besides, by the end of this research, readers can find some other aspects which can affect one’s colour vocabulary besides gender differences. At the end of the research, I can say that Lakoff’s theory about female and male differences in colour naming is more or less similar with the condition of FIB UI English students.